HUBUNGAN ANTARA EFIKASI DIRI DAN DUKUNGAN SOSIAL TERHADAP KECEMASAN BERTANDING PADA ATLET KARATE DOJO SEISHIN SETELUK - Adji Febriasyah; Maulidin; Sri Erni Muliyani (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2024)
This study aims to examine the relationship between self-efficacy and social support on competition anxiety among karate athletes at Dojo Seishin Seteluk. The research employed a quantitative method with a descriptive design, collecting data through questionnaires distributed to 12 karate athletes. The variables analyzed were self-efficacy, social support, and competition anxiety. Data analysis was performed using multiple linear regression with SPSS software. The results indicate that there is no significant relationship between self-efficacy, social support, and competition anxiety among the karate athletes. However, the study provides valuable insights into psychological factors that may influence athletic performance, showing a negative relationship between self-efficacy and competition anxiety. Therefore, it can be concluded that self-efficacy and social support, when considered simultaneously, do not significantly affect competition anxiety in karate athletes at Dojo Seishin Seteluk.